Pengaruh Kualitas Penetapan Pajak Dan Tindakan Penagihan Aktif Terhadap Pencairan Tunggakan Pajak - Rudi Hidayat; Charoline Cheisviyanny (Wahana Riset Akuntansi, 2013)
This study aimed to examine: (1) effect of the tax determination quality of the recovery of tax arrears and (2) effect of active tax collection of the recovery of tax arrears. This type of research is causative research. The population in this study is delinquent taxpayers who obtain sanction reduction decisions or objection / appeal decisions in 2010. The sample was determined by the random sampling method. Types of data used is secondary data obtained from the tax office primary Padang. The method of analysis used is double regression analysis. The results of this study indicate that tax determination quality have a significant positive effect to the recovery of tax arrears. Active tax collection also has have a significant positive effect to the recovery of tax arrears. Based on these results, it is suggested : 1) To improve the quality of the tax determination. Thus, the tax authorities must do tax audit properly through the stages, procedures, and guidelines established. 2) To improve active tax collection to get more tax arrears’ disbursement.Keywords: tax determination quality, active tax collection, recovery of tax arrears